The Production of a Documentary Recording Process on Group Theater Phenomena in São Paulo and in the Capitals of Brazil - Mate, Alexandre (2025)
This article describes some aesthetic and pedagogical characteristics of theater companies working in the state of São Paulo and in the Brazilian capitals. Since 2018, a group of researchers has established, through networks, contact with hundreds of companies, in order to learn more about their history, creative processes, most significant theoretical references, important partnerships and the role of theater for them. This text sums up some of these results.